Factors affecting the response of the premature neonates with respiratory distress syndrome to the surfactant - Elsaiti, Isaaida; Abdulmalek, Lubna (Libyan Journal of Science &Technology, 2022)
BACKGROUND: Respiratory distress syndrome (RDS) is a common problem in premature babies who born before 37 weeks of gestation. It occurs due to the lack of pulmonary surfactant, which is a phospho-lipoprotein produced by alveolar cells at the last stage of lung development. There are many risk factors of RDS among premature neonates including; born before the 28th week of gestation and Low birth weight. OBJECTIVES: To assess the response of the premature neonates admitted in Benghazi pediatric hospital with respiratory distress syndrome (RDS) to the surfactant therapy and factors affecting it. METHODS: The records of all respiratory distress premature neonates who admitted to the hospital during the year 2013, received surfactant (Survanta) 4 ml/kg under a sterile condition through special endotracheal tube and kept on a ventilator either continuous positive airway pressure (CPAP) or intermittent positive pulmonary ventilation (IPPV)were reviewed. RESULTS: The total number of cases with RDS and received surfactant therapy were 38 cases. 63% of them were born before 34-week gestational age, 84% of the cases their birth weight were less than 2.0 kg. About 55% of the respiratory distress premature neonates respond to the surfactant therapy and cured. The most significant factors affected their response were gestational age, birth weight, complications during pregnancy and the type of assisted ventilator. CONCLUSION: The response of premature neonates with RDS to the surfactant therapy can be improved by treating the pregnancy complications and using a continuous positive airway pressure ventilator.